Innovative Teaching Strategies in Madrasahs: Integrating Traditional and Digital Pedagogies for Enhanced Student Engagement - Arif Rohman Hakim (Islamic Journal of Teaching and Learning, 2025)
The development of digital technology has encouraged transformation in the education system, including in madrasas based on religious values. However, the process of integrating traditional and digital teaching methods still faces various challenges. This study aims to analyze the effectiveness of innovative teaching strategies that combine traditional and digital pedagogy to increase student engagement in madrasas. Using a qualitative approach with a case study method, data were collected through semi-structured interviews, observations, and documentation in several madrasas. Thematic analysis was conducted to identify patterns of student engagement and the impact of implementing hybrid teaching methods. The results show that hybrid teaching strategies not only improve student engagement and learning outcomes, but also help students understand the material more deeply through digital media that is interactive and relevant to modern learning contexts. However, challenges include limited access to technology and infrastructure readiness, which requires policy support and ongoing teacher training. This study provides practical recommendations for madrasas to adopt an adaptive, relevant, and balanced learning model between religious values and modern technology.